Airspace and the Takings Clause - Troy A. Rule (Washington University Law Review, 2012)
This Article argues that the United States Supreme Court’s takings jurisprudence fails to account for instances when public entities restrict private airspace solely to keep it open for their own use. Many landowners rely on open space above adjacent land to preserve scenic views for their properties, to provide sunlight access for their rooftop solar panels, or to serve other uses that require no physical invasion of the neighboring space. Private citizens typically must purchase easements or covenants to prevent their neighbors from erecting trees or buildings that would interfere with these non-physical airspace uses. In contrast, public entities can often secure their non-physical uses of neighboring airspace without having to compensate neighbors by simply imposing height restrictions or other regulations on the space. The Court’s existing regulatory takings rules, which focus heavily on whether a challenged government action involves physical invasion of the claimant’s property or destroys all economically beneficial use of the property, fail to protect private landowners against these uncompensated takings of negative airspace easements. In recent years, regulations aimed at keeping private airspace open for specific government uses have threatened wind energy developments throughout the country and have even halted major construction projects near the Las Vegas Strip. This Article highlights several situations in which governments can impose height restrictions or other regulations as a way to effectively take negative airspace easements for their own benefit. This Article also describes why current regulatory takings rules fail to adequately protect citizens against these situations and advocates a new rule capable of filling this gap in takings law. The new rule would clarify the Court’s takings jurisprudence as it relates to airspace and would promote more fair and efficient allocations of airspace rights between governments and private citizens.
Keywords: takings; airspace; easements; negative airspace easements